Pola Komunikasi Orang Tua dan Guru Dalam Membimbing Siswa Anak Berkebutuhan Khusus di SLB Negeri 1 Martapura - Fitriana, Rita Nur; Sanusi, Sanusi; Mardiana, Mardiana (CV. Green Publisher Indonesia, 2025)
The objectives of this study are (1) to find out the communication patterns of teachers and parents of students of children with special needs in SLB Negeri 1 Martapura, (2) to find out the inhibiting factors in the communication pattern between teachers and parents of students of children with special needs in SLB Negeri 1 Martapura and (3) to find out the solutions used in dealing with the inhibiting factors in the communication pattern between teachers and parents in dealing with students with special needs children in SLB Negeri 1 Martapura SLB Negeri 1 Martapura. The research method used in this study is a qualitative approach using data collection techniques in the form of observation, interviews and documentation. The research subjects used 5 informants from SLB Negeri 1 Martapura homeroom teachers and 5 informants from parents of children with special needs. The results of the study showed that the communication pattern used for children with special needs at SLB Negeri 1 Martapura was an interpersonal communication pattern and the communication pattern used by homeroom teachers to parents of children with special needs was interpersonal communication. The factors that inhibit interpersonal or interpersonal communication in dealing with children with special needs at SLB Negeri 1 Martapura are communication skills and emotional disturbances of children with special needs, the use of technology media that has not been maximized and the lack of attention from parents.